Managing Brazil’s Health System at municipal level against Covid-19: a preliminary analysis - Tasca, Renato (2022)
This qualitative, observational, and exploratory study was supported by quantitative data to analyze the Brazilian Unified Health System (SUS) response to Covid-19 in three Brazilian municipalities. We used semi-structured interviews to listen to and dialogue with managers of the cities analyzed, guided by a roadmap to explore the managers’ perception during the response to the pandemic, understand the motivations that guided their strategic choices, and visualize the weaknesses and potentials of the municipal system in a public health emergency. We conducted a qualitative analysis considering the critical points of the SUS response to the pandemic, including coordination and governance, surveillance and prevention, and the health services network. In the results, we present and discuss the main characteristics of the municipalities, the 2020 pandemic course, the response actions adopted, and submit an analysis of the response pattern of municipal SUS managers in the pandemic.